MANAGEMENT OF THE SOROGAN IN UNDERSTANDING THE KITAB KUNING IN ISLAMIC BOARDING SCHOOLS - Yakhsyallah, Achmad; Rostini, Deti; Khadijah, Ifah (Jurnal Konseling Pendidikan Islam, 2025)
Pondok pesantren (Islamic Boarding School), as a traditional Islamic educational institution, plays an important role in the preservation and development of Islamic studies, particularly through the teaching of the yellow book (kitab kuning). However, the use of classical Arabic and the depth of the material present unique challenges for students (santri) in the understanding process. This study aims to examine the management of the sorogan method in enhancing the understanding of the yellow book at Pondok Pesantren Ar-Risalah (West Bandung Regency) and Pondok Pesantren MUS Sarang (Rembang Regency). This research employs a qualitative descriptive approach with data collection techniques including in-depth interviews, field observations, and document analysis. The results indicate that structured sorogan management encompassing aspects of planning, organizing, implementation, and supervision positively impacts the improvement of students' abilities to comprehend the content of the yellow book. This method facilitates the creation of a learning environment that is individual, interactive, and adaptive to each student's capabilities. Challenges faced include the limited number of supervising teachers and the varying levels of students' understanding; however, these can be minimized through effective time management strategies and the use of simple technology in the teaching and learning process. The conclusion of this study emphasizes that systematic and adaptive management of the sorogan method is a potential alternative solution for enhancing the quality of yellow book learning in the pesantren environment.